Active Control over the Wettability from Superhydrophobic to Superhydrophilic by Electrochemically Altering the Oxidation State in a Low Voltage Range. Issue 12 (26th April 2017) - Zahiri, Beniamin; Sow, Pradeep Kumar; Kung, Chun Haow; Mérida, Walter
Abstract : Fast and reversible active control over the surface wettability of electrodeposited copper is achieved through electrochemical manipulation of the oxidation state. The switchable wettability described in this work allows for facile and precise control over the surface wettability, ranging from superhydrophobic (contact angle about 157°) to superhydrophilic (contact angle less than 10°) with a short response time. The rate of wetting transition and the desired contact angle can be precisely controlled by modulating the magnitude and duration of the applied potential. The wettability alteration is completely reversible when the sample is dried at ambient or heat‐dried at 100 °C. The heat‐drying does not impact the surface composition when compared to the samples dried at room temperature. The surface contains a mixture of CuO and Cu2 O as revealed by the surface composition analysis. The mechanism underlying the wetting alteration is based on the Faradaic phase transformation at the surface. An integrated droplet manipulation system is also demonstrated. The single‐step and additive‐free sample preparation is scalable and can be used to design smart surfaces and devices that require control over the wettability (e.g., liquid lenses, microfluidic devices, sensitive particulate matter handling systems, controlled filtration, and biomedical applications). Abstract : Tunable wettability on electrochemically responsive copper nanostructure is introduced. Superhydrophobic to superhydrophilic wetting behavior can be achieved by low voltage (<1.5 V) electrochemical transformation of the topmost copper oxide layer to metallic copper. The process is reversed upon exposure to air. An integrated droplet manipulation system is also demonstrated. The methodology is transferrable to biomedical solid particle handling and smart filtration.